Limites do modelo de ligação enzima-substrato “chave-fechadura” para o ensino de Ciências - Pelentir, Gabriel Felder (Universidade Federal de São Carlos, 2021)
A very common problem in contemporary society and evidenced by the current global health crisis, the growth of scientific illiteracy and the social and political problems arising from it .It shows nothing more than the failure of teaching, in general, to provide critical scientific education. In this work, it was assumed that teaching with a historical approach can be a viable solution to this problem. Therefore, the historical construction of enzyme-substrate binding models was analyzed in the Ludwik Fleck's epistemology perspective, also the way this subject is treated in two textbooks present in the PNLD. The method of collection and analysis used in this work was qualitative research through document analysis. It was concluded that textbooks, in addition to treating the subject in a completely ahistorical and fragmented way, fail to address concepts that are essential for a consistent understanding of enzyme-substrate binding models and enzymes in general. In this regard, a historical approach in the light of Ludwik Fleck can solve the problems related to content and contribute to the formation of more scientifically more critical citizens.
Limits of the “key-lock” enzyme-substrate connection model for science teaching
Keywords: História e filosofia da ciência; Ensino de ciências; Ludwik Fleck; Science history and philosophy; Science teaching; Ludwik Fleck; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM